Climate change and the end of the Classic period in Yucatán: Resolving a paradox - Dahlin, B.H.
Recent paleoecological research indicates that the collapse of Classic Maya civilization in the southern and central Maya Lowlands coincided with the onset of prolonged and severe drought conditions around a.d. 850. The northern Maya Lowlands is an area thatreceives much less rainfall today and probably did so throughout most of the recent past; nevertheless, many northern lowland sites not only persisted throughout the period of the drought but actually prospered under the hegemony of Chichen Itza. This paper attempts to resolve this obvious paradox by examining the adaptive responses made by the northern Maya. The northern lowlands had a slight edge in adapting to the climate change that apparently devastated the south because it had easy access to a diversity of resources that no doubt contributed to Chichen Itza's subsistence security and the enrichment of its realm. However, massive transformations in the political and religious domains were every bit as necessary to Chichen Itza's adaptive strategy. The seeming paradox of Chichen Itza's successful adaptation to environmental adversity represents a cautionary tale about the dangers of oversimplification that are inherent in environmental deterministic thinking. Paradoxes of this kind arise when the primacy of cultural factors in adaptive processes is ignored.